Challenges of sustaining growth in African aviation: the case of Jomo Kenyatta international airport. (11th July 2006) - Irandu, Evaristus M.; Rhoades, Dawna L.
The average annual growth in African passenger traffic throughout the 1990s was 7% and in a region where only one in every 20 people have access to air travel, the prospects for further growth are substantial. However, the region faces significant challenges in meeting this growth including infrastructure development, financing, safety, security, public policy and regional liberalisation. This paper explores efforts at Jomo Kenyatta International Airport, Nairobi, Kenya to meet these challenges and position itself as an East African hub.